Biliary fascioliasis: Management in a child using endoscopic retrograde cholangio pancreatography - Sandesh V Parelkar; Sanjay N Oak; Amit Maydeo; Beejal V Sanghvi; Prashant B Joshi; Nitin Chaubal; Rajasekhara T Patil; Subrat K Sahoo; Patel Jiwan Lal; Nandita Sampath; Avani Koticha (Wolters Kluwer Medknow Publications, 2013)
A 9-year-old boy presented with right upper abdominal pain and fever. The radiologic investigations revealed multiple cholangitic abscesses with cholangitis and worms in common bile duct. Endoscopic retrograde cholangio pancreatographic (ERCP) sphincterotomy, basketing, ballooning and extraction of Fasciola hepatica worms from the common bile duct were done.